1987
DOI: 10.1079/bjn19870005
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the measurement of 25-hydroxy vitamin D in human saliva

Abstract: 1. A competitive protein-binding assay for 25-hydroxy vitamin D (25-OHD) in saliva has been established by adaptation of that previously described for 25-OHD in serum (Fairney et al. 1979).2. Random values of salivary 25-OHD in patients attending hospital for venesection showed a wide range of results (105-1000 pg/ml, n 55). These values corresponded to 1.2% of the total serum values with which they showed a significant relation (r 0.45, P < 0.001).3. There was no relation between salivary 25-OHD and measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
(13 reference statements)
0
7
1
Order By: Relevance
“…Since the human corneal epithelium is capable of synthesizing vitamin D [9], we speculate that the increased level observed in the tears could be due to vitamin D produced by the corneal epithelium following exposure of the eye to UVB rays present in sunlight. Unlike tear fluid, 25-hydroxyvitamin D in the saliva (another non-invasive source for measuring vitamin D) was reported to be manifold lower than that of the serum [25, 26]. Hence, more detailed studies are required to confirm increased 25-hydroxyvitamin D in tear fluid and understand the source that contributes to it.…”
Section: Discussionmentioning
confidence: 99%
“…Since the human corneal epithelium is capable of synthesizing vitamin D [9], we speculate that the increased level observed in the tears could be due to vitamin D produced by the corneal epithelium following exposure of the eye to UVB rays present in sunlight. Unlike tear fluid, 25-hydroxyvitamin D in the saliva (another non-invasive source for measuring vitamin D) was reported to be manifold lower than that of the serum [25, 26]. Hence, more detailed studies are required to confirm increased 25-hydroxyvitamin D in tear fluid and understand the source that contributes to it.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS/MS has also been adapted to saliva samples, with initial small studies showing salivary 25(OH)D 3 to be well correlated with the serum levels (r 5 0.83 po0.01) despite lower concentrations attributable to the absence of 25(OH)D bound to DPB [87,88]. Larger studies investigating the validity of saliva samples and the impact of 25(OH)D 2 (amongst other issues) are necessary before widespread clinical use.…”
Section: (Oh)d In Alternative Biological Samplesmentioning
confidence: 99%
“…The link between vitamin D levels and caries is multifactorial and includes genetic, environmental, nutritional, and socioeconomic factors. There are detectable amounts of vitamin D in saliva ranging from 105 to 1,000 pg/ml, depending on the individual, diet, and time of day (18). One study found that increased serum vitamin D levels were associated with lower occurrence of dental maladies, including caries and hypomineralization (19).…”
mentioning
confidence: 99%